Determinants of Weight Evolution Among HIV-Positive Patients Initiating Antiretroviral Treatment in Low-Resource Settings. (1st October 2015) - Huis in 't Veld, Diana; Balestre, Eric; Buyze, Jozefien; Menten, Joris; Jaquet, Antoine; Cooper, David A.; Dabis, Francois; Yiannoutsos, Constantin T.; Diero, Lameck; Mutevedzi, Portia; Fox, Matthew P.; Messou, Eugene; et al.
Abstract : Background: In resource-limited settings, clinical parameters, including body weight changes, are used to monitor clinical response. Therefore, we studied body weight changes in patients on antiretroviral treatment (ART) in different regions of the world. Methods: Data were extracted from the "International Epidemiologic Databases to Evaluate AIDS, " a network of ART programmes that prospectively collects routine clinical data. Adults on ART from the Southern, East, West, and Central African and the Asia-Pacific regions were selected from the database if baseline data on body weight, gender, ART regimen, and CD4 count were available. Body weight change over the first 2 years and the probability of body weight loss in the second year were modeled using linear mixed models and logistic regression, respectively. Results: Data from 205, 571 patients were analyzed. Mean adjusted body weight change in the first 12 months was higher in patients started on tenofovir and/or efavirenz; in patients from Central, West, and East Africa, in men, and in patients with a poorer clinical status. In the second year of ART, it was greater in patients initiated on tenofovir and/or nevirapine, and for patients not on stavudine, in women, in Southern Africa and in patients with a better clinical status at initiation. Stavudine in the initial regimen was associated with a lower mean adjusted body weight change and with weight loss in the second treatment year. Conclusions: Different ART regimens have different effects on body weight change. Body weight loss after 1 year of treatment in patients on stavudine might be associated with lipoatrophy. Abstract : Supplemental Digital Content is Available in the Text.